2011
DOI: 10.1074/jbc.m111.232439
|View full text |Cite
|
Sign up to set email alerts
|

ICP34.5 Protein of Herpes Simplex Virus Facilitates the Initiation of Protein Translation by Bridging Eukaryotic Initiation Factor 2α (eIF2α) and Protein Phosphatase 1

Abstract: The ICP34.5 protein of herpes simplex virus type 1 is a neurovirulence factor that plays critical roles in viral replication and anti-host responses. One of its functions is to recruit protein phosphatase 1 (PP1) that leads to the dephosphorylation of the ␣ subunit of translation initiation factor eIF2 (eIF2␣), which is inactivated by infection-induced phosphorylation. As PP1 is a protein phosphatase with a wide range of substrates, the question remains to be answered how ICP34.5 directs PP1 to specifically de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 28 publications
0
95
0
Order By: Relevance
“…However, in support of the scaffolding role of the PP1-targeting subunits, we previously showed that yeast eIF2γ contains a PP1-binding motif that enables recruitment of the phosphatase PP1/ GLC7 to its substrate eIF2α via the eIF2 complex (25). A similar idea has been proposed for the HSV γ34.5 protein, which is able to interact with both PP1 and eIF2α (29).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, in support of the scaffolding role of the PP1-targeting subunits, we previously showed that yeast eIF2γ contains a PP1-binding motif that enables recruitment of the phosphatase PP1/ GLC7 to its substrate eIF2α via the eIF2 complex (25). A similar idea has been proposed for the HSV γ34.5 protein, which is able to interact with both PP1 and eIF2α (29).…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with this idea, deletion of residues 233-248 of the HSV γ34.5 protein (Fig. 3, green box), which shows similarity to GADD34, was shown to impair eIF2α binding (29). To determine whether there is an eIF2α-binding motif in the C-terminal region of GADD34, the amino acid sequences of CReP, γ34.5, and DP71L Fig.…”
Section: Gadd34 Promotesmentioning
confidence: 77%
See 1 more Smart Citation
“…ICP34.5 contributes to HSV-1 resistance to the antiviral effects of ␣/␤ interferon (72,73). Moreover, it recruits the serine/threonine-protein phosphatase PPP1CA to dephosphorylate the translation initiation factor EIF2A, thereby counteracting the host shutoff of protein synthesis involving double-stranded RNA-dependent protein kinase EIF2AK2 (74). Recently it has been shown that the interaction between ICP34.5 and C1QBP/p32 at late time points of infection leads to the disintegration of nuclear lamina and facilitates nuclear egress of HSV-1 particles (75).…”
Section: Fig 1 Proteome Characterization During Hsv-1 Infection By mentioning
confidence: 99%
“…Us3 interrupts IFN-␤ production by phosphorylation of IRF3 (9). Our previous studies also discovered that the virulent factor ICP34.5 binds with both protein phosphatase 1 and eIF-2␣, facilitating viral protein synthesis (10,11).…”
mentioning
confidence: 99%